An Interactive E-Worksheet Using the STAD Model on Phase Changes of Matter to Fourth Grade Students - Ni Luh Putu Gautami; Anak Agung Gede Agung; Ida Bagus Gede Surya Abadi (International Journal of Elementary Education, 2025)
The low student learning outcomes in IPAS (Natural and Social Sciences) learning are caused by the use of less varied teaching methods and the limited utilization of interactive digital media. This study aims to develop an interactive E-Worksheet based on the Student Team-Achievement Division (STAD) model on the topic of Changes in the States of Matter in IPAS learning. This research is a research and development (R&D) study using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects included experts in design, content, instructional design, learning media, and 13 fourth-grade elementary school students. The instruments used in this study were questionnaires and tests. The data were analyzed using descriptive quantitative statistics and a one-sample t-test. The results showed that the learning media had a very high quality (score > 90%) based on expert validation and product testing, and the t-test results showed that tcount = 1.899 > ttable = 1.782. It can be concluded that the development of interactive E-Worksheet based on the STAD model has been proven to improve student learning outcomes and promote active and collaborative engagement in IPAS learning. The implication of this study is that this learning media can help teachers create a more contextual, enjoyable learning process that aligns with the Merdeka Curriculum and meets the needs of 21st-century students.